Analisis Dan Perancangan Software Aplikasi Sistem Informasi Akuntansi Harga Pokok Produksi - Feri Andrian; Sudjana (Indonesian Accounting Literacy Journal, 2021)
During the COVID-19 Pandemic, PT Cakra Terang had to adjust its information system. The Accounting Information System for Cost of Production becomes the object of this research. The results of the comparative analysis of the Company's method and the Full Costing method, there is an average difference of Rp.550, -. This is because the basis difference in costing in the Company's method is less clear, compared to the Full Costing method. Thus, the Full Costing method is used in the proposed Design of Accounting Information System Applications for Cost of Production with the System Development Life Cycle and Rapid Application Development methods. This application can manage the recording and calculation of the production process and produce a final report on the Cost of Production and selling prices as well as managing the inventory of raw materials. This application can be accessed online which is equipped with access rights.